1997
DOI: 10.1016/s0092-8674(00)81909-1
|View full text |Cite
|
Sign up to set email alerts
|

Bipolar Localization of the Replication Origin Regions of Chromosomes in Vegetative and Sporulating Cells of B. subtilis

Abstract: To investigate chromosome segregation in B. subtilis, we introduced tandem copies of the lactose operon operator into the chromosome near the replication origin or terminus. We then visualized the position of the operator cassettes with green fluorescent protein fused to the Lac1 repressor. In sporulating bacteria, which undergo asymmetric cell division, origins localized near each pole of the cell whereas termini were restricted to the middle. In growing cells, which undergo binary fission, origins were obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
348
3
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 346 publications
(372 citation statements)
references
References 33 publications
20
348
3
1
Order By: Relevance
“…The events involved in chromosome segregation and partitioning include resolution of chromosome dimers resulting from recombinational crossovers between sister chromosomes, decatenation of interlinked daughter chromosomes, and movement of daughter chromosomes away from each other (43). Recent evidence suggests that bacterial chromosome segregation is an active mitosis-like process and that the origin of replication (oriC) of the E. coli and B. subtilis chromosome has a specific orientation during the cell cycle (9,10,20,44). Thus, in newborn cells oriC is oriented toward a cell pole; after replication of this region, one of the two origins moves rapidly toward the opposite pole of the cell while the termination region remains centrally located (10,44).…”
Section: Discussionmentioning
confidence: 99%
“…The events involved in chromosome segregation and partitioning include resolution of chromosome dimers resulting from recombinational crossovers between sister chromosomes, decatenation of interlinked daughter chromosomes, and movement of daughter chromosomes away from each other (43). Recent evidence suggests that bacterial chromosome segregation is an active mitosis-like process and that the origin of replication (oriC) of the E. coli and B. subtilis chromosome has a specific orientation during the cell cycle (9,10,20,44). Thus, in newborn cells oriC is oriented toward a cell pole; after replication of this region, one of the two origins moves rapidly toward the opposite pole of the cell while the termination region remains centrally located (10,44).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, important progress has been made in the understanding of the active chromosomal segregation process in vegetative and sporulating B. subtilis cells (Ireton et al, 1994;Sharpe and Errington, 1996;Glaser et al, 1997;Lin et al, 1997;Webb et al, 1997). It has been shown that 30% of the chromosome containing oriC has a centromere-like function that, during binary fission and sporulation, migrates actively towards the cell poles (Sharpe and Errington, 1996;Wu and Errington, 1994;Glaser et al, 1997;Webb et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that 30% of the chromosome containing oriC has a centromere-like function that, during binary fission and sporulation, migrates actively towards the cell poles (Sharpe and Errington, 1996;Wu and Errington, 1994;Glaser et al, 1997;Webb et al, 1997). Because accurate segregation is affected in spoOJ mutant strains (Ireton et al, 1994;Sharpe and Errington, 1996), the SpoOJ protein was a prime candidate for being involved in the chromosomal segregation process.…”
Section: Discussionmentioning
confidence: 99%
“…These problems are circumvented by a novel technique, which uses the lac or tet repressor fused to a fluorescent protein to specifically decorate tandem repeats of the cognate repressor binding site inserted at a chromosomal locus of interest Straight et al, 1996;Michaelis et al, 1997;Lau et al, 2003]. Using these two approaches, it was shown that bacteria possess mechanisms to orient the replication origin and terminus towards opposite poles in newborn cells Webb et al, 1997;Niki and Hiraga, 1998;Jensen and Shapiro, 1999;Fogel and Waldor, 2005]. This finding already indicates some degree of order within the nucleoid.…”
Section: Spatial Arrangement Of the Bacterial Chromosomementioning
confidence: 99%